Extradural Spinal Arachnoid Cysts - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2007)
A 14-year-old boy with multiple spinal arachnoid cysts and paraplegia, and 37 similar cases in the literature are reviewed by neurosurgeons and radiologist at Univ of Sao Paulo, Brazil.